A rare cause of dysphagia: CREST syndrome - J., Varunkumar; Sachdeva, Sheenu; Jaiswal, Shubhlaxmi Atmaram (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Reporting a case of a 29-year-old female patient who came to the outpatient department with features of CREST syndrome. This case report illustrates the ENT presentation of CREST syndrome. A 29 year female with features of CREST syndrome (Calcinosis+, Raynaud’s phenomena +, oesophageal dysmotility+ sclerodactyly+ and Telangiectasias+, with no pulmonary hypertension) with ANA titres positive. Complete blood count, serum electrolytes, renal function tests, liver function tests, chest X-ray ,barium swallow ,ECG was done. Rigid oesophagoscope was used for the bougie dilatation of the stricture of oesophagus and was conservatively treated for her symptoms and being followed up at present. GI disturbances such as heartburn, dysphagia or respiratory complaints. Example: dyspnoea are occasionally the first manifestations of the disease. Dysphagia, manifested by various abnormal swallowing sensation, is intially caused by impaired oesphageal motility but later can result from gastroesophageal reflux disease and secondary stricture formation. Hereby concluding that any patient coming in OPD with similar features as mentioned above we should have a differential diagnosis of CREST syndrome and limited cutaneous scleroderma, yet it is a rare case.